Pemanfaatan Media Sosial sebagai Sarana Komunikasi Pemasaran untuk Meningkatkan Brand Addiction - Milanita Puspita Pertiwi; Muhammad Isnaini; Lasmery Rosentauly Maissalinya Girsang (IPM2KPE, 2022)
This study aims to find out how to use social media as a means of marketing communication for Femiaura Beauty to increase brand addiction, especially in the Tangerang Serpong area. The research method used is a qualitative method with observation and interviews. The interviews conducted were validated using triangulation of data sources. Respondents in this study were owners of Femiaura Beauty, 3 employees of Femiaura Beauty, and 7 customers of Femiaura Beauty. The collected data is analyzed using The Circular Mode of Somee analysis model, including elements of share, optimize, manage, engagement. The results showed that Femiaura beauty has used social media as a means of marketing communication well. Sales generated from social media are increasing. Many customers also promote word of mouth, review on social media, and recommend to their friends. In addition, with the existence of social media, customers become easier to communicate, no need to come to the treatment center. In conclusion, social media can be used as a means of communication in increasing brand addiction. Keywords: Brand Addiction, E-Marketing, Social Media